Descemet membrane endothelial keratoplasty in multifocal pseudophakic eyes - Pereira,Nicolas Cesário (2018)
ABSTRACT Purpose: This report describes the use of Descemet membrane endothelial keratoplasty for the management of endothelial decompensation after multifocal intraocular lens implantation. Methods: In this retrospective study, we reviewed and assessed the surgical outcomes of 9 patients (9 eyes) who underwent Descemet membrane endothelial keratoplasty after multifocal intraocular lens implantation. Results: Corneal edema occurred due to Fuchs endothelial corneal dystrophy (n=3), pseudophakic bullous keratopathy (n=3), Descemet’s membrane detachment (n=2), and toxic anterior segment syndrome (n=1). The Descemet membrane endothelial keratoplasty surgeries were uneventful in all eyes, but rebubbling procedures were necessary in 2 eyes. One month after the surgery, all the corneas were clear. After 6 months, excluding 1 eye with amblyopia, the mean distance corrected visual acuity was 0.10 logMAR, with all eyes achieving 0.18 logMAR or better. Conclusions: This is the first report of Descemet membrane endothelial keratoplasty after multifocal intraocular lens implantation, and it suggests that good results can be achieved without multifocal intraocular lens exchange.